2010
DOI: 10.1111/j.1538-7836.2010.03937.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thrombin generation in patients with cirrhosis‐induced coagulopathy

Abstract: To cite this article: Gatt A, Riddell A, Calvaruso V, Tuddenham EG, Makris M, Burroughs AK. Enhanced thrombin generation in patients with cirrhosis-induced coagulopathy. J Thromb Haemost 2010; 8: 1994-2000 Summary. Background: Prothrombin time (PT) and the international normalized ratio (INR) are still routinely measured in patients with liver cirrhosis to ÔassessÕ their bleeding risk despite the lack of correlation with the two. Thrombin generation (TG) assays are global assays of coagulation that are showing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
176
1
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(209 citation statements)
references
References 28 publications
22
176
1
8
Order By: Relevance
“…13 The TGT was used to demonstrate that plasma from patients with stable cirrhosis generates thrombin at a normal or even increased rate despite prolonged PT/INR and PTT values. 13,23 The TGT is still primarily a research tool and not validated for predicting bleeding risk in patients with liver disease. Early studies showed that TEG guided factor replacement reduced red cell transfusions and the volume of plasma infused during liver transplantation.…”
Section: Global Tests Of Hemostasismentioning
confidence: 99%
“…13 The TGT was used to demonstrate that plasma from patients with stable cirrhosis generates thrombin at a normal or even increased rate despite prolonged PT/INR and PTT values. 13,23 The TGT is still primarily a research tool and not validated for predicting bleeding risk in patients with liver disease. Early studies showed that TEG guided factor replacement reduced red cell transfusions and the volume of plasma infused during liver transplantation.…”
Section: Global Tests Of Hemostasismentioning
confidence: 99%
“…More recently, it was proposed that TGA, performed in the presence or absence of thrombomodulin and with results expressed as a ratio between the 2 measurements, could be a sensitive parameter to detect hypercoagulability (18 ). This approach was instrumental to show that patients with cirrhosis possess a certain degree of hypercoagulability (31)(32)(33). This observation paved the way to the treatment of patients with cirrhosis and portal vein thrombosis with low molecular weight heparin (LMWH) (34 ), a treatment that was until recently considered a contraindication in these patients because of the perceived risk of bleeding.…”
Section: Application Of Tga To Increase Understanding Of Coagulation mentioning
confidence: 99%
“…Patients with advanced fibrosis have significantly lower levels of protein C and antithrombin (Tripodi et al, 2005). Furthermore, this partial deficiency of anticoagulant proteins in those with advanced chronic liver disease is accompanied by enhanced thrombin generation within these patients (Gatt et al, 2010), together resulting in a procoagulant state. This could in part explain why the historical assumption that cirrhotics are 'auto-anticoagulated' and therefore protected against developing peripheral thromboembolic disease has now been demonstrated to be untrue.…”
mentioning
confidence: 99%